Competitiveness of Indonesia’s export products with IJEPA cooperation framework - Sukarniati, Lestari; Lubis, Firsty Ramadhona Amalia; Hossain, MD Modabber (Universitas Ahmad Dahlan, 2024)
Bilateral cooperation between Indonesia and Japan Economic Partnership Agreement (IJEPA) is a form of bilateral cooperation between Indonesia and Japan that carries the concept of the Economic Partnership Agreement (EPA). With one of IJEPA's goals in the form of capacity building, Bilateral cooperation between Indonesia and Japan Economic Partnership Agreement (IJEPA) is a form of bilateral cooperation between Indonesia and Japan that carries the concept of the Economic Partnership Agreement (EPA). With one of IJEPA's goals in the form of capacity building, IJEPA provides space for both parties to collaborate in order to increase the competitiveness of Indonesian producers. Problems in trying to maximize the impact of the IJEPA agreement on increasing domestic product product industries have encouraged Indonesia to be able to determine what products are worthy of being superior products in the context of international trade conducted with Japan. This study analyzes the trade and competitiveness of Indonesian products using Revealed Symmetric Comparative Advantage (RSCA) and Product Mapping.The results of the product mapping analysis show that there are 3 commodities that are included in the top five highest comparative advantage in 2003, 2013 and 2021, namely HS 11 commodities (Milling Industrial Products; Malt; Starch; Inulina; Wheat Gluten) HS code 21 (Extracts, essences and concentrates, from coffee, tea or mate and preparations with a basis of these products or with a basis of coffee, tea or mate) and HS code 25 (Salt; Sulfur; Soil and Stone; Plaster, Cal and Cement). This shows that these three products can be used as specialization products for Indonesia's trade with Japan.